Smart Janus titanium mesh used as a diode for both liquid droplet and air bubble transport. (6th September 2021) - Zhang, Shi-Ming; Zhang, Yu-Ping; Liu, Ming-Lin; Wang, Bing-Xing; Liu, Peng-Fei; Bai, Xiuzhi; Cui, Cheng-Xing; Qu, Ling-Bo
Abstract : A Janus titanium mesh was fabricated with unidirectional transport for both liquid droplets in air and gas underwater. Abstract : Design and fabrication of Janus interface materials as diodes for both liquids and gases are a great challenge in the field of materials science. Here, a Janus titanium mesh with superhydrophobicity and high oleophobicity was fabricated using economical and environmentally friendly electrochemical etching and wet-chemistry methods. Switchable, spontaneous, and unidirectional transport ability for both water and oil fluids was realized in the smart mesh by ultraviolet (UV) irradiation. Unidirectional fluid transport only occurred for fluids with specific surface tension values, and the fluid selectivity was dependent on the UV irradiation time. Underwater bubble unidirectional permeation through the mesh was also achieved using a mesh irradiated for approximately 7 h. More importantly, the mechanism is proposed and elucidated in detail, and the proposed mechanism can more reasonably explain the antigravity unidirectional transport of liquid droplets.